Sistem Informasi Pengolahan Data Penjualan Dan Peramalan Pembelian Setiap Pelanggan Dengan Metode Trend Projection Berbasis Web - Nanny Raras Setyoningrum; Giandicka; Naufal Muhammad Kautsar (Jurnal Bangkit Indonesia, 2021)
PT. Aldora Sukses Perkasa is an ice cream distributor located on Jalan Martadinata Tanjungpinang. PT. Aldora Sukses Perkasa usually only makes sales by salesmen by visiting shops that are already customers. The problems faced by the company are the absence of an online sales system so that it can make it easier for customers to order the items needed and the customer purchase forecasting system that can predict customer purchases in the next period. With the development of “SISTEM INFORMASI PENGOLAHAN DATA PENJUALAN DAN PERAMALAN PEMBELIAN SETIAP PELANGGAN DENGAN METODE TREND PROJECTION BERBASIS WEBSITE PADA PT. ALDORA SUKSES PERKASA TANJUNGPINANG“ this very helpful in processing data, information on inventory, sales reporting and reporting of inventory data